Evaluation of adipogenesis over time using a novel bioabsorbable implant without the addition of exogenous cells or growth factors - Sunghee Lee; Shuichi Ogino; Yoshihiro Sowa; Kenta Yamamoto; Yuki Kato; Maria Chiara Munisso; Susumu Saito; Manabu Shirai; Tetsuji Yamaoka; Naoki Morimoto (Regenerative Therapy, 2024)
Background: Breast reconstruction is crucial for patients who have undergone mastectomy for breast cancer. Our bioabsorbable implants comprising an outer poly-l-lactic acid mesh and an inner component filled with collagen sponge promote and retain adipogenesis in vivo without the addition of exogenous cells or growth factors. In this study, we evaluated adipogenesis over time histologically and at the gene expression level using this implant in a rodent model. Methods: The implants were inserted in the inguinal and dorsal regions of the animals. At 1, 3, 6, and 12 months post-operation, the weight, volume, and histological assessment of all newly formed tissue were performed. We analyzed the formation of new adipose tissue using multiphoton microscopy and RNA sequencing. Results: Both in the inguinal and dorsal regions, adipose tissue began to form 1 month post-operation in the peripheral area. Angiogenesis into implants was observed until 3 months. At 6 months, microvessels matured and the amount of newly generated adipose tissue peaked and was uniformly distributed inside implants. The amount of newly generated adipose tissue decreased from 6 to 12 months but at 12 months, adipose tissue was equivalent to the native tissue histologically and in terms of gene expression. Conclusions: Our bioabsorbable implants could induce normal adipogenesis into the implants after subcutaneous implantation. Our implants can serve as a novel and safe material for breast reconstruction without requiring exogenous cells or growth factors.